Biofertilizacion del cultivo de la habichuela (Phaseolus vulgaris) en condiciones de organoponico - Diaz Bofill, C.=700 1 Gonzalez Perez, M.; Alvarez Marquez, J.I.; Laurencia Silva, M.
(Es, En)
Ilus., 9 ref.
Keywords: PHASEOLUS VULGARIS; BIOFERTILIZACION; AZOSPIRILLUM; MICORRIZAS ARBUSCULARES VESICULARES; CUBA; HABICHUELA; ORGANOPONICO